2020
DOI: 10.1051/0004-6361/202039098
|View full text |Cite
|
Sign up to set email alerts
|

Lifting the curtain: The Seyfert galaxy Mrk 335 emerges from deep low-state in a sequence of rapid flare events

Abstract: Context. The narrow-line Seyfert 1 galaxy Mrk 335 was one of the X-ray brightest active galactic nuclei, but it has systematically faded since 2007. Aims. We report the discovery with Swift of a sequence of bright and rapid X-ray flare events that reveal the emergence of Mrk 335 from its ultra-deep multiyear low state. Methods. Results are based on our dedicated multiyear monitoring of Mrk 335 with Swift. Results. Unlike other bright active galactic nuclei, the optical–UV is generally not correlated with the X… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 58 publications
3
17
0
Order By: Relevance
“…The consistency of this result with those in the literature further 12 We highlight the low-luminosity PG quasar Mrk 335 in Figures 2-4 because it has displayed extreme X-ray variability on short timescales (e.g. Komossa et al 2020), and thus the measurement of 𝛼 ox , He EW, and 𝐿 2500 might be highly variable. This one quasar, however, does not affect greatly the fitted relationships.…”
Section: The Relationships Between 𝛼 Ox He Ew and 𝐿 2500supporting
confidence: 85%
See 1 more Smart Citation
“…The consistency of this result with those in the literature further 12 We highlight the low-luminosity PG quasar Mrk 335 in Figures 2-4 because it has displayed extreme X-ray variability on short timescales (e.g. Komossa et al 2020), and thus the measurement of 𝛼 ox , He EW, and 𝐿 2500 might be highly variable. This one quasar, however, does not affect greatly the fitted relationships.…”
Section: The Relationships Between 𝛼 Ox He Ew and 𝐿 2500supporting
confidence: 85%
“…sample was constructed using quasars from multiple different samples that often had large temporal gaps between the observations. Despite the differences in the epoch of observation (generally > 1 year), only the low-luminosity quasar Mrk 335 was identified to have extreme X-ray variability (Komossa et al 2020). The extreme X-ray variability of Mrk 335 causes this object to be an extreme outlier with respect to the rest of the data, particularly in Figures 3 and 4.…”
Section: Results Of This Workmentioning
confidence: 94%
“…Gallo et al 2018;Tripathi et al 2020). However, since the coronal optical emission lines, which are supposed to be driven by EUV and soft X-rays, do not vary much in Mrk 335 (Grupe et al 2008), it was suggested that such huge X-ray variability is due to the variable column density and covering factor of the X-ray absorbers near the SMBH (Komossa et al 2020). Therefore, even considering the above uncertainties of 𝐿 bol , the Eddington ratio of Mrk 335 is still high.…”
Section: Eddington Ratio Of Mrk 335mentioning
confidence: 99%
“…doublepeaked emission lines, systematic line shifts, periodic behaviour or dual bright compact radio cores, for the existence of binary black hole system in Mrk 335. Another possible mechanism causing the S-shaped jet would be the warped disk near the jet launching site, arising from non-axisymmetric radiation (Pringle 1996) or accretion events, the latter of which would be interesting given that Mrk 335 is accreting at such high Eddington ratio and has been detected for several flares in optical and X-rays during the past decades (Komossa et al 2020). However, the current data set is not adequate to confirm the validity of they S-shaped jet structure in Mrk 335.…”
Section: Parsec-scale Bipolar Jet Structurementioning
confidence: 99%
See 1 more Smart Citation